Mathematics and physical reality: The theme of the absence of the “Transcendental Signifi ed” in the language of modern fundamental science - Duplinskya, Yuliya Mikhailovna (Известия Саратовского университета: Новая серия. Серия Философия. Психология. Педагогика, 2023)
Introduction. It is argued that today the expansion of mathematics into the field of physical reality is not being performed in line with the classical paradigm, but in line with the linguistic turn of non-classical philosophy. Theoretical analysis. Such aspect of nature’s “non-fittability” into the conceptual network of mathematics as the problem of asymmetry is explored. It is stated that the world, constructed according to the logic of ideal mathematical symmetries, passes into a state called unmanifested in Hinduism. In the same direction the concept of J. Baudrillard is considered, where the structures of ideal reversibility are supposed to be the most radical way to destroy what exists and the symbol of nothingness. Accordingly, ideal mathematical symmetry describes states thatcannot exist as a physical reality. The settlement of “dense” reality in the mathematical language of theoretical physics is seen in irrational, transcendent and imaginary numbers, in which the ideal reversibility of mathematical operations is violated. Conclusion. The search for “supersymmetry” is regarded as a variation of general language problems. Ideal symmetry in mathematics, “supersymmetry” in fundamental physics, like any “transcendental signified”, can only exist “under the sign of strikeout”. Variations on the theme of diff erance are revealed here. A generating source of difference, according to J. Derrida, is always on the other side of the language.